Performance of a novel fluorogenic probe assay for the detection of extended-spectrum-beta-lactamase or plasmid AmpC beta-lactamase-producing Enterobacterales directly from simulated blood culture bottles - Park, MiJung; Park, Yeon-Joon; Yu, Jinkyung; Lee, Jieun; Ahn, Dae-Ro; Min, Sun-Joon (ELSEVIER, 2020)
Resistance to third generation cephalosporins is widely disseminated in Enterobacteriaceae mainly because of extended-spectrum-beta-lactamases (ESBL), plasmid AmpC beta-lactamases (PABL), and hyper-production of chromosomal AmpC beta-lactamases. Here, we evaluated the performance of rapid test using novel fluorogenic probe assay in simulated blood cultures and compared the results with the phenol red assay using a total of 172 characterized isolates (39 ESBL producers, 13 PABL producers, and 120 susceptible isolates). We prepared a pellet by centrifugation and washing, which can also be used for identification with MALDI-TOF directly from positive blood cultures. After that, we mixed the pellet with fluorogenic probe and measured the fluorescent signal using fluorometer. The fluorogenic probe assay showed higher sensitivity than the phenol red assay (96.2% vs. 71.2%, p < .0001) in 172 simulated blood culture bottles especially in detecting PABL (84.6% vs. 0%, p = .0026) and the turnaround time was 1.5 h. This fluorogenic probe assay, combined with the direct identification of pathogens, could be very useful for rapid identification of isolates and detecting cephalosporin resistance caused by ESBL and PABL directly from positive blood cultures.
Keywords: RAPID DETECTION; EPIDEMIOLOGY; IMPACT